Formulation and physicochemical characterization of azithromycin-loaded cubosomes - Hoorieh Zaker; Somayeh Taymouri; Abolfazl Mostafavi (Wolters Kluwer Medknow Publications, 2023)
Background and purpose: Azithromycin (AZ) is a macrolide antibiotic that is soluble in saliva pH; its bitter taste can be well sensed, decreasing the ability of the patient to get the drug. Thus, handling such a bitter taste is challenging in developing the oral formulation. A wide range of methods has been applied to tackle this problem. Cubosomes are considered nanoparticles forming cubic three-dimensional structures with a taste-masking effect. This research aimed to apply cubosomes to mask AZ's bitter taste. Experimental approach: Cubosomes which contained AZ were obtained by applying the film hydration method. Design expert software (version 11) was then employed for optimizing cubosomes that contained the drug. The encapsulation efficiency, particle size as well as polydispersity index of drug-loaded cubosomes were then subjected to evaluation. Assessment of particle morphology was done through SEM. The antimicrobial qualities of AZ-loaded cubosomes were then assessed by utilizing the disc diffusion method. Then, the taste masking study was carried out by referring to human volunteers. Finding/Results: AZ-loaded cubosomes were spherical in terms of shape and in the 166-272 nm range, with a polydispersity index of 0.17-0.33 and encapsulation efficiency of 80-92%. The results related to the microbial culture revealed that the antimicrobial qualities related to AZ-loaded cubosomes were like those of AZ. The results obtained by taste evaluation also revealed that the cubosomes could well mask the drug's bitter taste. Conclusion and implications: These findings, thus, revealed that while the antimicrobial impact of AZ is not under the influence of loading in cubosomes, its taste could be well improved.